2016
DOI: 10.1016/j.trf.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Auditory localisation of conventional and electric cars: Laboratory results and implications for cycling safety

Abstract: When driven at low speeds, cars operating in electric mode have been found to be quieter than conventional cars. As a result, the auditory cues which pedestrians and cyclists use to assess the presence, proximity and location oncoming traffic may be reduced, posing a safety hazard. This laboratory study examined auditory localisation of conventional and electric cars including vehicle motion paths relevant for cycling activity. Participants (N = 65) in three age groups (16-18, 30-40 and 65-70 year old) indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Older cyclists may have had problems with auditory detection and localisation of other road users. Previous research found that the elderly are less accurate at auditory detection and localisation of moving cars than younger adults (Mendonça et al, 2013;Stelling-Kończak et al, 2016). It is important that future studies address the issue of older cyclists' not being able to hear other road users.…”
Section: Age Differencesmentioning
confidence: 97%
See 1 more Smart Citation
“…Older cyclists may have had problems with auditory detection and localisation of other road users. Previous research found that the elderly are less accurate at auditory detection and localisation of moving cars than younger adults (Mendonça et al, 2013;Stelling-Kończak et al, 2016). It is important that future studies address the issue of older cyclists' not being able to hear other road users.…”
Section: Age Differencesmentioning
confidence: 97%
“…Slow moving (hybrid) electric cars are also detected later and localised less accurately by vulnerable road users than conventional cars, especially in environments with low ambient noise (Stelling-Kończak, Hagenzieker & Van Wee, 2015). Furthermore, electric cars driven at low speeds are localised less accurately than conventional cars, as found in a recent laboratory study including vehicle motion paths relevant for cycling activity (Stelling-Kończak et al, 2016). Also studies with drivers of electric cars suggest that cyclists have problems hearing these vehicles (Cocron & Krems, 2013;Hoogeveen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As crossing is a task which requires many attentional resources that use the same (limited) visual channel [89], the presence of a high number of objects which detract attention from the road requires pedestrians to work harder to keep a focus on traffic and make safe crossing decisions [90]. Additionally, ambient noise from background sources can make it harder to determine a vehicle's travel path [91][92][93] and has been reported to affect pedestrians' perception of the surrounding environment [94]. Finally, accomplishing the crossing task with poor weather and visibility conditions was found to be more demanding than in the baseline scenario.…”
Section: Self-reported Workloadmentioning
confidence: 99%
“…Pedestrians' crossing behaviour, e.g., speed and perception of the surrounding environment can be affected by the level and quality of surrounding noise [95]. Ambient noise also has the potential of masking the sound of approaching vehicles, leading pedestrians to hear vehicle noises with insufficient safety margins [93]. The validation and standardization of eHMIs and different cue modalities would greatly benefit from visual and auditory stimuli closer to a real traffic environment for increased realism as well as to test the efficacy of different designs and multimodal cues where elements of the surrounding scene could interfere with successful AV-pedestrian communication.…”
Section: Presence and Sicknessmentioning
confidence: 99%
“…Specifically, EVs and hybrid electric vehicles (HEVs), which operate in electric mode at low speeds, have quieter engines at these speeds. This, coupled with the increased use of low noise road surfaces, could pose a threat to the safety of vulnerable road users [ 9 ] who rely on their senses of sight and hearing to navigate road traffic safely in urban environments, since the paucity of auditory cues associated with the approach of these vehicles at low speeds increases the risk of pedestrian accidents [ 10 , 11 , 12 ]. Recent work has focused on analysing the relationship between the age of younger pedestrians and the ability to correctly collect and interpret visual and auditory signals from road traffic [ 13 , 14 ], which indicates that in children under 11 years of age the interpretation of auditory signals can be erroneous.…”
Section: Introductionmentioning
confidence: 99%